Translation in Romania: Steps towards recognition and professionalization - Greere, Anca (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2010)
The article proposes a survey of the Romanian context with regard to the translation profession, especially with reference to directions of development after 2007, i.e., the year of Romania’s accession to the EU. The research focuses on the configuration of the Romanian translation market and community in order to understand how the combination of international integration, academic efforts and involvement of professionals have made it possible to generate in a relatively short time a genuine marketplace and one that is rapidly making its mark on the European and international levels. The key questions are related to the level of awareness of the general population and academic institutions regarding translation market issues, the degree of recognition of language professions on a social and economic level and the extent to which professionalization has taken place to include a collective professional conscience. To these aims the following aspects will be reviewed: the underlying principles that build up the current context for translation in Romania, the developments in training, market practices and the relation to the European profession and academic environment.